The Influence of Brand Image, Brand Equity, and Lifestyle on Purchase Decisions at Excelso Coffee SunCity Mall Sidoarjo.: Pengaruh Brand Image, Brand Equity, dan Gaya Hidup terhadap Keputusan Pembelian pada Excelso Coffee SunCity Mall Sidoarjo - Nurwanto, Virgiawan; Indayani, Lilik (Indonesian Journal of Law and Economics Review, 2023)
This research aims to investigate the impact of Brand Image, Brand Equity, and Lifestyle on purchasing decisions at Excelso Coffee in Suncity Mall, Sidoarjo. Employing a quantitative approach, the study utilized nonprobability sampling (accidental sampling) to gather responses from 100 consumers at Excelso Coffee in Suncity Mall, East Java. Data analysis involved multiple linear regression using SPSS 22.0. The findings demonstrate that brand image, brand equity, and lifestyle individually influence purchasing decisions. Furthermore, when considered simultaneously, brand image, brand equity, and lifestyle collectively have a significant impact on purchasing decisions. This study underscores the importance of these factors in influencing consumer choices. The concise and impactful title for this research could be "Influence of Brand Factors and Lifestyle on Consumer Purchasing Decisions. Highlights: Impactful Factors: Brand image, brand equity, and lifestyle influence consumer purchasing decisions. Quantitative Approach: The study employs a quantitative methodology to analyze the relationships between these factors. Collective Influence: The research highlights the combined effect of brand-related elements and lifestyle on consumer choices. Keywords: Brand Image, Brand Equity, Lifestyle, Purchasing Decisions, Consumer Behavior